EXTH-79. HIJACKING A NEURODEVELOPMENTAL EPIGENOMIC PROGRAM IN METASTATIC DISSEMINATION OF MEDULLOBLASTOMA. (14th November 2022) - Zou, Han; Poore, Bradley; Brown, Emily; Yash, Patel; Hu, Zhongliang; Li, Xuejun; Pollack, Ian F; Friedlander, Robert M; Hainer, Sarah; Taylor, Michael; Hu, Baoli
Abstract: Normal brain development relies on precise genetic and epigenetic spatiotemporal regulation of gene expression. How dysregulation of neurodevelopment relates to medulloblastoma, the most common pediatric brain tumor, remains elusive. Here, we uncovered a novel neurodevelopmental epigenomic program that regulates Purkinje cell migration in developing cerebellum is hijacked to induce tumor metastatic dissemination in medulloblastoma. Integrating publicly available datasets with our in-house data, unsupervised analyses revealed that BAF60C/SMARCD3, a subunit of SWI/SNF chromatin remodeling complex, promotes tumor cell migration in vitro and metastasis in vivo. Based on analyzing the single-cell RNAseq data of cerebellum developmental trajectory in mice and humans, aligning with the medulloblastoma patients' datasets, we found that BAF60C/SMARCD3 regulated DAB1-mediated Reelin signaling is involved in Purkinje cell positioning during cerebellum development and medulloblastoma metastasis by orchestrating the cis -regulatory elements (CREs) at the DAB 1 gene locus. Moreover, analysis of spatiotemporal gene expression and chromatin architecture in the human and mouse cerebellum demonstrated that transcription activity of the BAF60C/SMARCD3-DAB1 circuit is downregulated in a mature state of cerebellar development, however, is upregulated in metastatic medulloblastoma. We further identified that a core set of transcription factors, enhancer of zeste homolog 2 (EZH2) and nuclear factor I X (NFIX), bi-directionally control BAF60C/SMARCD3 transcriptional regulation by coordinating with the CREs at the BAF60C/SMARCD3 gene locus to form a chromatin hub during developing cerebellar development and medulloblastoma metastatic dissemination. Highly expressed BAF60C/SMARCD3 activates the Reelin/DAB1 signaling pathway downstream Src kinase, which was validated in the pair-wised primary and metastatic tumors from medulloblastoma patients. Preclinical medulloblastoma mouse models revealed that inhibiting Src activity reduces tumor cell migration and metastatic dissemination at a lower and safe dose. Together, these data deepen our understanding of how the developmental program influences disease progression and provide an opportunity for the development of therapeutics for this devastating brain cancer in children.